2012
DOI: 10.1002/jsfa.5637
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cocoa, soy, oats and fish oil on metabolic syndrome in rats

Abstract: BACKGROUND: The effect of functional foods alone or in combination (cocoa + soy + oats + fish oil) on hepatic damage in rats affected with metabolic syndrome was investigated. RESULTS: Rats that were given cocoa showed a decrease in the levels of triglycerides (TGs) and glucose (63 and 32% respectively) as well as a decrease in blood pressure (15%). Animals fed with soy showed a reduction of 21% in total cholesterol, 15% in blood pressure and 44% in TGs, while feeding oats reduced the concentration of TGs by 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…This effect of whole soy flour of lowering the triglyceride level can be attributed to the soy protein and or the presence of isoflavones and dietary fiber [18,25]. The hypotriglyceride property of soybean was observed in other studies as well, with animals and humans on balanced diets [25-29]. It was interesting to note that whole soy flour in the cafeteria diet decreased the liver fat (p < 0.05), countering the effect of the high-fat diet.…”
Section: Discussionmentioning
confidence: 97%
“…This effect of whole soy flour of lowering the triglyceride level can be attributed to the soy protein and or the presence of isoflavones and dietary fiber [18,25]. The hypotriglyceride property of soybean was observed in other studies as well, with animals and humans on balanced diets [25-29]. It was interesting to note that whole soy flour in the cafeteria diet decreased the liver fat (p < 0.05), countering the effect of the high-fat diet.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the specific intervention positively influenced genes involved in peroxisomal and mitochondrial fatty acid β-oxidation such as acyl-CoA oxidase (COA), the mitochondrial trifunctional protein α subunit (hydroxyacyl-CoA dehydrogenase/3-ketoacyl-CoA thiolase/enoyl-CoA hydratase) and fatty acid transport into the mitochondria by carnitine palmitoyltransferase 1A (CPT-1A) by increasing their expression in the liver. Further improvements on hepatic and serum lipid metabolism parameters due to soyabean administration were described in other studies (18)(19)(20)(21)(22)(23) . Specifically, among the mentioned studies, Barrios-Ramos et al (18) and Potu et al (21) indicated that the administration of powder and oil of soyabean induced improvements on hepatic steatosis and the hepatic inflammation marker c-reactive protein, respectively.…”
Section: Glycine Max/soyabeanmentioning
confidence: 63%
“…Further improvements on hepatic and serum lipid metabolism parameters due to soyabean administration were described in other studies (18)(19)(20)(21)(22)(23) . Specifically, among the mentioned studies, Barrios-Ramos et al (18) and Potu et al (21) indicated that the administration of powder and oil of soyabean induced improvements on hepatic steatosis and the hepatic inflammation marker c-reactive protein, respectively. In addition, proteins involved in lipid synthesis pathways (fatty acid synthase (FAS), acetyl-coenzyme A carboxylase α, Stearoyl-CoA desaturase-1, fatty acid elongase 6, sterol regulatory element binding protein 1 (SREBP1) and carbohydrate-responsive element-binding protein) were down-regulated as a consequence of soyabean administration, thus suggesting an improvement in lipid metabolism pathways (19,24) .…”
Section: Glycine Max/soyabeanmentioning
confidence: 63%
See 2 more Smart Citations